1998
DOI: 10.1093/emboj/17.6.1779
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the ubiquitous CNC-bZIP transcription factor, Nrf-1, results in anemia and embryonic lethality in mice

Abstract: The CNC-basic leucine zipper (CNC-bZIP) family is a subfamily of bZIP proteins identified from independent searches for factors that bind the AP-1-like cis-elements in the β-globin locus control region. Three members, p45-Nf-e2, Nrf-1 and Nrf-2 have been identified in mammals. Expression of p45-Nf-e2 is largely restricted to hematopoietic cells while Nrf-1 and Nrf-2 are expressed in a wide range of tissues. To determine the function of Nrf-1, targeted disruption of the Nrf-1 gene was carried out. Homozygous Nr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
271
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(277 citation statements)
references
References 36 publications
5
271
0
1
Order By: Relevance
“…Genomic clones containing the nrf1 gene have been described (11). We generated a targeting construct containing a 5Ј loxP site inserted into the nrf1 intron-3, and a phosphoglycerate kinase 1 (PGK-1) promoter-driven neomycin resistance gene cassette flanked by a 3Ј loxP site downstream of the terminal exon.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic clones containing the nrf1 gene have been described (11). We generated a targeting construct containing a 5Ј loxP site inserted into the nrf1 intron-3, and a phosphoglycerate kinase 1 (PGK-1) promoter-driven neomycin resistance gene cassette flanked by a 3Ј loxP site downstream of the terminal exon.…”
Section: Methodsmentioning
confidence: 99%
“…Mice deficient in Nrf1 function die during development (11). Analysis of nrf1 and nrf1::nrf2 mutant cells suggests that Nrf1 is also involved in the oxidative stress response (12,13).…”
mentioning
confidence: 99%
“…Our findings also raise the intriguing question of whether Nrf proteins and SKN-1 might have similar developmental functions. Nrf2 −/− mice are viable, but Nrf1 knockouts caused either an erythroid defect, or abnormal gastrulation and lack of mesoderm (Farmer et al 1997;Itoh et al 1997;Chan et al 1998). The latter phenotype is reminiscent of the maternal skn-1 defect.…”
Section: Skn-1 and Oxidative Stress Resistance Genes And Development 1889mentioning
confidence: 99%
“…In 1996, Chan et al [24] showed that NRF2 is not essential in developmental processes but later this have been challenged [25][26][27]. SKN-1, the Caenorhabditis elegans ortholog of NRF2, is known to be important in the mesoderm and endoderm formation [28].…”
Section: Functional Analysis Of the Nrf2 Interactomementioning
confidence: 99%